A RESEARCH TO DETERMINE THE RELATIONSHIP BETWEEN DIGITAL TRANSFORMATION AND MOTIVATION: THE CASE OF SİRNAK - İdin, Orhan; Sönmez, Ramazan Vedat (Berrin ONARAN, 2024)
With the change and transformation in the field of technology, products and applications such as digitalization, artificial intelligence technologies, internet and robot machines have begun to show their effects in every aspect of our lives. One of the areas where the effects of technological developments are seen is working life. These technological advances have brought about many changes in working life. Change in organizational structures, digitalization in the workforce, improvement in service conditions, increase in productivity, speed in communication, labor saving are the first effects of digital transformation. Digital transformation may contain some opportunities but also threats. In particular, the concern that unemployment will increase as a result of technological progress, that many valid professions and skills will disappear, and that new job groups will be formed creates anxiety and anxiety among employees. It is evaluated that this anxiety and anxiety may affect the level of success, performance and motivation of the employee. The purpose of this study; The aim is to determine the relationship between digital transformation and employee motivation and to determine employees' perceptions and motivation levels towards digital technologies according to their demographic characteristics. The research was conducted for 166 employees at Dedaş company operating in Şırnak province. Survey technique was used in data collection, and the data obtained was analyzed with the SPSS 23.0 package program. As a result of the research; A significant relationship was found between the participants' perception of digital transformation and employee motivation, between their graduation status and motivation levels, and between their graduation status and digital transformation perceptions.

Teknoloji alanında yaşanan değişim, dönüşüm ile birlikte, dijitalleşme, yapay zeka teknolojileri, internet, robot makineler gibi ürün ve uygulamalar yaşantımızın her alanında etkilerini göstermeye başlamıştır. Teknolojik gelişmelerin etkilerin görüldüğü alanlardan biri de çalışma yaşamıdır. Söz konusu teknolojik ilerlemeler çalışma yaşamında birçok değişimi beraberinde getirmiştir. Örgüt yapılarının değişimi, işgücünde dijitalleşme, hizmet koşullarında gelişme, verimlilikte artış, iletişimde hız, iş gücünden tasarruf dijital dönüşümün ilk etkileri olarak karşımıza çıkmaktadır. Dijital dönüşüm birtakım fırsatlarla birlikte tehditleri de bünyesinde barındırabilmektedir. Özellikle teknolojik ilerleme sonucu işsizliğin artacağı, birçok geçerli meslek ve becerilerin yok olacağı, yeni iş gruplarının oluşacağı endişesi iş görenler arasında kaygı yaratmakta, endişeye yol açmaktadır. Bu kaygı ve endişenin iş gören başarı, performans ve motivasyon düzeyini etkileyebileceği değerlendirilmektedir. Bu çalışmanın amacı; dijital dönüşüm ve iş gören motivasyonu arasındaki ilişkiyi belirlemek, iş görenlerin demografik özelliklerine göre dijital teknolojilere yönelik algılarını ve motivasyon düzeylerini tespit etmektir. Araştırma Şırnak ilinde faaliyette bulunan Dedaş işletmesindeki 166 çalışana yönelik yapılmıştır. Veri toplama işleminde anket tekniği kullanılmış, elde edilen veriler SPSS 23.0 paket program ile analize tabi tutulmuştur. Araştırma sonucunda; katılımcıların dijital dönüşüm algısı ile iş gören motivasyonu arasında, mezuniyet durumları ile motivasyon düzeyleri arasında ve mezuniyet durumları ile dijital dönüşüm algıları arasında anlamlı bir ilişki bulunmuştur.
DİJİTAL DÖNÜŞÜM VE MOTİVASYON ARASINDAKİ İLİŞKİYİ BELİRLEMEYE YÖNELİK BİR ARAŞTIRMA: ŞIRNAK İLİ ÖRNEĞİ
Keywords: Information Systems Organisation and Management; Bilgi Sistemleri Organizasyonu ve Yönetimi